Assessment of Municipalities Performances in Slovenia - Alenka Pandiloska JURAK; Uroš PINTERIČ (Transylvanian Review of Administrative Sciences, 2012)
Due to the ongoing public administration reform process in Slovenia, different models for assessing performance of different levels of public administration, including municipalities, are introduced. However, no stable and systematically model, that could be used for systematic evaluation of municipalities performance was developed so far. Due to this reason, the evaluation model called ALENKA was developed. Results are showing that municipalities with different backgrounds can be compared and ranked according to their performance on the basis of this model.